2018
DOI: 10.15294/biosaintifika.v10i3.17126
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Potentials of Button Mushroom (Agaricus bisporus) on Alloxan-Induced Diabetic Rats

Abstract: Button mushrooms (Agaricus bisporus) is an edible mushroom that is most widely cultivated in the world. It contains bioactive compounds that might provide beneficial effects on diabetes mellitus patient. The study aimed to determine the effects of A. bisporus administration on the blood glucose, and malondyaldehyd (MDA) levels as well as superoxide dismutase (SOD) activity of alloxan-induced diabetic rats. This study was also conducted to determine the secondary metabolites produced by A. bisporus. The method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Earlier studies show that mushrooms are rich in ß-D-glucans, ß-glucan, a type of dietary fiber that shows promising health benefits against T2DM [80]. Mushroom extracts from Pleurotus species [56], Boletu [58], Grifola frondosa [81], Agaricus bisporus [38], Hericium erinaceus [63], and Ganoderma lucidum [82] regulate the synthesis of glycogen and lowers blood glucose levels by regulating gene expression of glycogen synthase kinase (GSK-3 ß), glycogen synthase (GS) and glucose transporter 4 (GLUT4) in liver and muscle. Therefore GSK-3 ß could be identified as an insulin-mediated GSregulated negative regulator [83].…”
Section: Blood Glucose-lowering Effect Of Polysaccharidementioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies show that mushrooms are rich in ß-D-glucans, ß-glucan, a type of dietary fiber that shows promising health benefits against T2DM [80]. Mushroom extracts from Pleurotus species [56], Boletu [58], Grifola frondosa [81], Agaricus bisporus [38], Hericium erinaceus [63], and Ganoderma lucidum [82] regulate the synthesis of glycogen and lowers blood glucose levels by regulating gene expression of glycogen synthase kinase (GSK-3 ß), glycogen synthase (GS) and glucose transporter 4 (GLUT4) in liver and muscle. Therefore GSK-3 ß could be identified as an insulin-mediated GSregulated negative regulator [83].…”
Section: Blood Glucose-lowering Effect Of Polysaccharidementioning
confidence: 99%
“…Several studies have proven that mushrooms, especially Pleurotus spp. [56], Grifola frondosa [81], Agaricus bisporus [38], Hericium erinaceus [63], and Ganoderma lucidum [65] have significant blood glucose-lowering effect, as they delay the absorption of glucose and therefore improves hyperglycaemic condition [78].…”
Section: Inhibition Of Glucose Absorptionmentioning
confidence: 99%
“…Mushrooms have been found to have high concentrations of β-D-glucans, especially β-glucan, a form of dietary fiber that has shown positive effects in combating type 2 diabetes [ 112 ]. Gene expression of glycogen synthase kinase (GSK-3 β), glycogen synthase (GS), and glucose transporter 4 (GLUT4) in the liver and muscle is regulated by mushroom extracts from Pleurotus species [ 49 ], Agaricus bisporus [ 54 ], Ganoderma lucidum [ 113 ], etc., leading to decreased blood glucose levels. As a result, GS kinase 3 beta (GSK-3 β) could be a negative regulator of GS mediated by insulin [ 114 ].…”
Section: The Preventive Mechanistic Approach Of Mushrooms Against Dia...mentioning
confidence: 99%
“…Multiple studies have shown that mushrooms, particularly Pleurotus spp. [ 49 ], A. bisporus [ 54 ], and G. lucidum [ 59 ], significantly reduce blood glucose levels by delaying the body’s absorption of glucose [ 110 ].…”
Section: The Preventive Mechanistic Approach Of Mushrooms Against Dia...mentioning
confidence: 99%
“…In addition, mushrooms have been described to possess beneficial health effects such as gut microbiota modulation [10,11], reduction in brain oxidative stress [10], anti-obesogenic effects and liver steatosis prevention [12,13], anti-cancer [14,15], anti-inflammatory [16][17][18], and antimicrobial [19][20][21], among others [6][7][8]. Moreover, they have antioxidant, anti-hyaluronidase, anti-tyrosinase, anti-elastase, and anti-collagenase activity, making them suitable for use as cosmetic ingredients [22].…”
Section: Introductionmentioning
confidence: 99%